"The remediation policy after mining works in the Kyrgyz Republic". (June 2019) - Makhmudova, Gulzhan; Matsui, Kenichi
Abstract: According to the National Statistical Committee of the Kyrgyz Republic, the mining industry in 2014 had more than 53.9% of the value of all industrial products, while the share of the mining industry in GDP in the same year was more than 10%. Under the former Soviet Union, the mining industry was of great importance in the Kyrgyz Republic. In the last 20 years, discoveries of large gold deposits and other valuable minerals brought Canadian and other international corporations to exploit. These companies operate without clearly detailed land remediation law and regulations. Many unresolved and partially resolved issues on disposal, reclamation of disturbed lands after mining, including radioactive waste, have been dealt in a case-by-case manner. This paper examines the current situation of the post-mining land remediation policy in the Kyrgyz Republic. It focuses on the legal and political frameworks for land remediation after mining works. The topic about remediation has not gained much academic attention in the Kyrgyz Republic and other developing countries, especially as it is related to remediation policies, but this matter is urgent in the country. The Kyrgyz government has updated some strategies to deal with land remediation issues. However, this paper reveals that these recent efforts are still short of securing the health of the environment, which is the bedrock of the national wealth today and tomorrow. The discussion also shows how laws and regulations define and stipulate about remediation issues. This paper reveals that post remediation regulations do not give a well-defined guideline for administering remediation actions. Consequently, the land law that stipulates procedure on remediation activities are not well explained and do not provide detailed information. In establishing this remediation policy, the first step to be taken is to clearly define land remediation. The second step is to identify the types of remediation processes. The third step is to create new guidelines for appropriate remediation works by clarifying responsible agencies and establishing an adequate fund for all the works required, including monitoring and skill training. Highlights: The first step to be taken is to clearly define land remediation; The second step is to identify the types of remediation processes; The third step is to create new guidelines for appropriate remediation works by clarifying responsible agencies and establishing an adequate fund for all the works required, including monitoring and skill training.